(untitled) (Research, Society and Development, 2023)
The discipline of Science is usually shown as a subject that has an excess of expository methodologies in the public school system, since specified obstacles persist for the effective integration of active methodologies and Digital Technologies, whether in school or outdoors. What are the active methodologies employed in elementary education that are capable of promoting improvements in the Science teaching and learning process? This research has the general objective of analyzing the use of active methodologies in the process of teaching and learning Science in public schools in a city located in the Mesoregion of Eastern Maranhão, Brazil. The methodological path of this work initially passed through the exploratory sieve of journals and related documents on active methodologies. And, later, in a field research with seven Science teachers working in urban or rural spaces, in a descriptive and qualitative approach, through an electronic form allocated in Google Docs. The work pointed out the use and preference of active methodologies in Science teaching, as well as possible obstacles to the realization of a greater variability of active methodologies and the appreciation of education professionals.